Dividend-Yield Trading Strategies: Evidence from the Chinese Stock Market - Huang, Chin-Sheng; You, Chun-Fan; Lin, Hueh-Chen (International Journal of Economics and Financial Issues, 2014)
Utilizing the data from the Shanghai and Shenzhen exchanges between the periods of 2005 to 2011, this paper explores whether trading strategies based on dividend-yield are effective in the Chinese stock market. Under market risk-adjusted, we find an abnormal return for the samples of cash and dual dividend-yield. However, dual dividend-yield samples only significantly display abnormal returns in the three-factor model. Finally, incorporating the price momentum into the three-factor model the abnormal returns still appear in the dual-dividend-yield samples. When the sample is further divided into high- and low-moment periods, the evidence indicates that abnormal returns mainly stem from the low-moment subsample. Therefore, we conclude that the sources of dividend yields anomaly cannot be fully explained by market, size, value, and momentum factors. Moreover, the abnormal returns can become even stronger during the low-moment period. Keywords: dividend yield; trading strategies. JEL Classifications: G11; G12